Effect of citric acid and acetic acid on the performance of broilers - Islam, MZ; Khandaker, ZH; Chowdhury, SD; Islam, KMS (Journal of the Bangladesh Agricultural University, 2010)
An experiment was conducted with commercial broilers to investigate the effects of feeding citric acid, acetic acid and their combination on their performance and to determine the economic competence of using citric acid and acetic acid in broiler rations. A total number of 108 one day old straight run broiler chicks were distributed to four dietary treatments i.e. 0 % citric or acetic acid (A), 0.5% citric acid (B), 0.5% acetic acid (C) and their combinations 0.5% citric acid and 0.5% acetic acid (D). The birds were reared in cages. Body weight gains, feed conversion ratio (FCR), mortality, dressing yield and carcass characteristics were recorded. The performance showed significant increase in body weight gain (P<0.05) when compared with the control during 0-5 weeks of age on 0.5% citric acid (B). Feed consumption increased (P<0.05) at 2nd and 3rd weeks of age on 0.5% citric acid (B). Feed conversion was found higher (P<0.05) during 0-5 weeks of age in treatment B when compared to those of the other treatments. Carcass characteristics were not affected by dietary treatments. The highest mortality was found in treatment A and treatment C due to excessive hot. It may be concluded that use of 0.5% citric acid in the diet of broilers may have better performance in respect of live weight gain and feed conversion. Keyword: Acetic acid; Citric acid; Broiler performance DOI: 10.3329/jbau.v6i2.4828 J. Bangladesh Agril. Univ. 6(2): 315-320, 2008